Road safety assessment on North Luzon Expressway using blackspot analysis - Ramos, Louise C.; Sigua, Ricardo G. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
With the increasing number of road deaths and casualties in the modern-day, road safety is an issue that needs to be addressed. Road safety is often mitigated through road crash prevention and road crash reduction. This study focuses on road crash reduction using blackspot analysis, wherein the researcher's main purpose is to determine the blackspots or hazardous locations in the North Luzon Expressway (NLEX). This was done by collecting and analyzing road crash data and traffic volume data for the last three years, and using Setting Benchmark Method to find said hazardous locations- a statistical process on determining blackspots by arranging all crashes with casualties in decreasing frequency, with respect to equal road segments. This method is suitable for developing countries like the Philippines, and when budget for improvements is constrained. Further, two case studies were done from the identified blackspots. And causal factors were determined by correlating the accident occurrences in the area with that of traffic flow and design. Possible mitigating measures were suggested depending on the findings. From the study, the researcher was able to point out 19 blackspots, of kilometer stretch each. The top two of which were near or on the major toll plazas to and from Metro Manila. The others were concentrated from Sta Rita to San Simon, Pampanga.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Traffic safety; Traffic accidents; Express highways -- Philippines